The secret life of political parties. A comparative study of candidate selection in African democracies - Mac Giollabhuí, Shane (Trinity College (Dublin, Ireland). Department of Political Science, 2009)
Every political party has three lives: a public life, a private life and a secret life. Publicly, parties campaign for office and, if elected, form governments. Privately, parties attract funding, formulate policy positions and announce candidacies. These first two lives are formal, strictly regulated and transparent affairs. Secretly, however, partisans lead a third, underground life: donations are solicited covertly, faction bosses scratch and manoeuvre for position; malcontents hatch plots to topple leaders; and subversives scheme against the constitutional order. This dissertation is about single part of the secret life of political parties. Our research question is: how do political parties, competing in divided societies, select parliamentary candidates, and does variation in such selection mechanisms influence the demography of parliamentary parties and the cohesion of political parties.
Keywords: Political Science, Ph.D.; Ph.D. Trinity College Dublin.